Entrepreneurship the Disney Way. - Goldsby, Michael G.; Mathews, Rob. (Milton : Routledge, 2018)
This book focuses on the business story of Walt Disney and the company he built. Combining a unique blend of entrepreneurship, creativity, innovation, and a relentless drive to bring out the best in his teams, Walt Disney created one of the most successful ventures in business history. Outlining the specific processes of the company, Goldsby and Mathews provide the reader with the tools they need to embrace their own entrepreneurial leadership style, to lead effectively, to be more innovative, and to build a successful organization. Through the lens of Disney, the reader learns the fundamentals of entrepreneurship, innovation, and leadership. Beginning with a general introduction to the concepts relevant to the entrepreneurial organization today, the book examines how Disney built his empire and how the company remains an industry leader. The book also provides the opportunity to take the Entrepreneurial Leadership Instrument, which measures one's style in leading entrepreneurial ventures. The book is divided into two parts: Part I provides an overview of Disney's entrepreneurial journey, including the topics of vision, risk-taking, financing, and human resource management; Part II examines the company's transition from a family business into a global operation, including topics such as succession planning and strategy. Part II also explores Disney Parks and Resorts, the part of the company that interacts directly with customers, including topics such as culture, employee engagement, customer service, and customer experience. Entrepreneurship the Disney Way brings entrepreneurship, innovation, and leadership to life through the compelling story of one of the most recognizable businessmen and companies of our time. The authors' interviews with high-level executives provides the reader with a rare inside look into the way his company functions. Disney fans, executives, and students of entrepreneurship, innovation, and leadership will find it a delightful and informing read.
Cover; Half Title; Title; Copyright; Dedication; CONTENTS; Acknowledgments; Introduction; PART 1 Walt Disney, Entrepreneur; 1 The Artist Years; 2 The Scientist Years; 3 The Builder Years; 4 The Evangelist Years; PART 2 Corporate Entrepreneurship at the Walt Disney Company; 5 Leaders in the Post-Walt Disney Era; 6 The Entrepreneurial Spirit of Disney Parks and Resorts; 7 Guest Engagement and Experience at Disney Parks and Resorts; Index.
OCLC-licensed vendor bibliographic record.
Keywords: Walt Disney Company; Disney, Walt, -- 1901-1966.; Businessmen -- United States -- Biography; Entrepreneurship -- United States; Creative ability in business -- United States; BUSINESS & ECONOMICS -- Entrepreneurship; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- General